Corporate Donations in the Context of Covid-19: Insights on Trust and Policy Innovation Opportunities - Victorino, Guilherme (Ital Publication, 2024)
This study aims to investigate the determinants of corporate donations during the initial phase of the Covid-19 pandemic, focusing on the Portuguese context. It explores the interplay between pandemic-related factors, corporate structures, recipient profiles, and media coverage on the levels of corporate donations. In the absence of publicly available data, a comprehensive database of corporate donations was constructed by analyzing over six thousand news pieces from various media sources between March and May 2020. The database comprises 1171 donations from 709 different institutions. The relationship between corporate donations and multiple variables was examined, including the epidemiological progression of the pandemic, corporate ownership structures, recipient characteristics, and media coverage. Our analysis reveals that during the initial wave of the Covid-19 pandemic in Portugal, corporate donations were predominantly made by large companies, primarily directed toward their local regions. Notably, nearly 93% of all donations were allocated to the National Health System. PPEs and hospital equipment were the preferred donation items among the contributing companies. These findings shed light on the factors influencing corporate donation behavior during emergency situations and provide valuable insights into trust levels within the healthcare system. This study contributes to the existing literature by offering a unique exploration of corporate donation behavior during the Covid-19 pandemic, specifically in Portugal. The comprehensive dataset and findings provide novel insights into the factors shaping corporate donation decisions during crises. Doi: 10.28991/ESJ-2024-08-05-010 Full Text: PDF